2021
DOI: 10.1002/fuce.202000157
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐doped graphene prepared by low‐temperature thermal treatment as an electrocatalyst support for methanol oxidation

Abstract: In this study, functionalized graphene is used as a carbon-based material to support platinum-ruthenium bimetallic nanoparticles and to improve methanol oxidation reaction activity due to the enhanced physical and electrical properties of graphene. First, surface oxidation is used for creating oxygen functional groups, and then nitrogen doping by thermal treatment with ammonia as the nitrogen precursor. Platinum-ruthenium alloy nanoparticles are dispersed by the impregnation reduction method on the support mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The larger ECSA indicated good dispersion of metal nanoparticles over the N‐doped graphene support 40 . In addition to, nitrogen‐doped graphene due to the improved electrical conductivity of support and better interaction between metal and support showed the highest ECSA 41 . In a study, the ECSA of the Pt nanoparticles on N‐doped graphene support is approximately 78% higher than that of the Pt nanoparticles on graphene support, which is attributed to the superior dispersion of the Pt nanoparticles on N‐doped support 42 .…”
Section: Resultsmentioning
confidence: 94%
“…The larger ECSA indicated good dispersion of metal nanoparticles over the N‐doped graphene support 40 . In addition to, nitrogen‐doped graphene due to the improved electrical conductivity of support and better interaction between metal and support showed the highest ECSA 41 . In a study, the ECSA of the Pt nanoparticles on N‐doped graphene support is approximately 78% higher than that of the Pt nanoparticles on graphene support, which is attributed to the superior dispersion of the Pt nanoparticles on N‐doped support 42 .…”
Section: Resultsmentioning
confidence: 94%
“…e synthesis process is continued for 12 hours at ambient temperature to complete the reduction reaction. Finally, the electrocatalyst has been washed and centrifuged several times and dried at 60°C in a vacuumed oven for 12 hours [2].…”
Section: Electrocatalyst Synthesismentioning
confidence: 99%
“…Different clean energy technologies have been evaluated in recent years to replace the current energy systems, which use fossil fuels [1]. Among different power generation technologies with lower greenhouse gas emissions in comparison with the conventional fossil fuel-based systems, fuel cells have some advantages [2]. e fuel cells convert the chemical energy of the fuel directly into heat and power through a set of electrochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies demonstrated that the Pt-M nanoparticles with ordered structures showed promising improvement in the activity and stability of the catalyst. 25,26 For a bimetallic Pt-M alloy system (M = Ru, 27,28 Ni, 29 Cu, 30,31 Pb, 32 Co, 33,34 Sn, 35 etc. ), the addition of M can promote the adsorption and activation decomposition of water at a lower potential and provide adsorbed hydroxyl groups (OH ads ), which serve as oxidants to transform the toxic species (CO ads ) into CO 2 by oxidizing.…”
Section: Introductionmentioning
confidence: 99%